CHILD NUTRITION AND GROWTH MONITORING IN MOLDOVA: CHALLENGES AND INTERVENTIONS - Sheik Mohamed S. H. (JTH: Journal of Technology and Health, 2025)
This study investigates the prevalence of childhood malnutrition in rural Moldova, with a particular focus on the factors influencing nutritional outcomes and the effectiveness of growth monitoring programs. A mixed-methods approach was used, combining both quantitative data from a cross-sectional survey and qualitative insights gathered through semi-structured interviews with mothers, healthcare workers, and community leaders. The survey revealed that 27% of children under five were stunted, while 16% were wasted, with the highest prevalence observed in lower-income households. Maternal education was found to be a key determinant of child nutrition, as children of mothers with secondary education or higher had significantly lower rates of malnutrition. The study also identified gaps in the effectiveness of growth monitoring programs, with follow-up care often inadequate. This research provides valuable insights for public health interventions aimed at reducing childhood malnutrition in rural Moldova and offers broader implications for similar contexts in Eastern Europe and Central Asia. The findings emphasize the need for integrated strategies that include poverty alleviation, education, and improved healthcare infrastructure to combat childhood malnutrition effectively.